2008
DOI: 10.1139/f07-197
|View full text |Cite
|
Sign up to set email alerts
|

Long-term trends in zooplankton of Dorset, Ontario, lakes: the probable interactive effects of changes in pH, total phosphorus, dissolved organic carbon, and predators

Abstract: Time trends in abundance, body size, species richness, and species composition indicate that crustacean zooplankton communities of southern Canadian Shield lakes changed between 1980 and 2003. Total abundance did not decline despite reductions in total phosphorus, but all other metrics changed. Species richness declined in Harp Lake (Ontario, Canada) following its Bythotrephes invasion, but richness increased in three other lakes. Average cladoceran body length increased from 0.6 to 1.0 mm in seven of the lake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
94
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(100 citation statements)
references
References 104 publications
6
94
0
Order By: Relevance
“…When nutrient levels are higher, competition pressures decrease and smaller individuals can proliferate. TP levels are currently declining in many Ontario lakes (Dillon & Molot 2005) and, consistent with our observations, a trend towards larger mean cladoceran body size with decreasing TP has been observed for Crosson, Dickie, Harp, and Plastic lakes for the time period of 1980-2003 (Yan et al 2008b).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…When nutrient levels are higher, competition pressures decrease and smaller individuals can proliferate. TP levels are currently declining in many Ontario lakes (Dillon & Molot 2005) and, consistent with our observations, a trend towards larger mean cladoceran body size with decreasing TP has been observed for Crosson, Dickie, Harp, and Plastic lakes for the time period of 1980-2003 (Yan et al 2008b).…”
Section: Discussionsupporting
confidence: 89%
“…For example, it can impair the visual ability of size-selective predators (Brooks & Dodson 1965). This suggests that larger Cladocera species should predominate in high DOC lakes due to decreased fish predation (Yan et al 2008b). However, our study demonstrated an opposing pattern where, on average, larger cladocerans occurred in lakes with lower DOC concentrations.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations